Effectiveness of the Use of Stop Motion Animation Learning Media in Understanding Historical Materials at Elementary School - Rohmiyah, Omi; Sakti, Asri Wibawa (LPPM Universitas Jenderal Achmad Yani, 2022)
Learning media is a success factor in the learning process. The use of interesting media is able to make students more focused in understanding the subject matter. The purpose of this study was to determine the effectiveness of stop motion animation learning media in understanding historical material for elementary school students. This study used a single subject activity method with a pre-test and post-test design. The subjects of this study were ten sixth grade elementary school students. Based on the post-test results, it shows that stop motion animation videos are very effective in increasing students' understanding of historical material. Based on the results of the pre-test and post-test showed a significant increase in students' understanding of historical material. The results of this study showed that the use of stop motion animation media was very effective in improving the understanding of class VI student's elementary school in historical material about the proclamation moments. This happens because stop motion is an interesting medium with simple explanations that make the subject matter easier to understand.